Distribution of pests of blueberries in South Africa and re-description and behaviour of the blueberry bud mite Acalitus vaccinii (Eriophyidae) - Ngubane, Nompumelelo Pretty (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.